Okay, here we have this:
Considering the provided sentences, we are going to apply the law of syllogism, so we obtain the following:
Let us remember that the law of Syllogism says that:
(1) If p , then q . And (2) If q , then r .
Then we can derive that: (3) If p , then r .
Applying:
(1) If the dog jumps in the lake, then it gets wet. (R->S)
(2) If the dog gets wet, then it can't come in the house. (S->T)
We can derive that:
(3) If the dog jumps in the lake, then it can't come in the house. (R -> T)